1991
DOI: 10.2307/1177001
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Formal Schooling to the Increase in Intellectual Capital

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 130.237.165.40 on Tue, 06 Oct 2015 14:23:24 UTC All use subject to JSTOR Terms and Conditions The Contribution of Formal Schooling t o the Increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 7 publications
1
14
0
4
Order By: Relevance
“…The study showed that students who had the most academically oriented education gained more in general intelligence compared to those with the least amount of academic education. Several similar studies have been carried out on Swedish data (e.g., Balke-Aurell, 1982;Gustafsson, in press;Husén & Tuijnman, 1991). There also are other such studies, several of which are Scandinavian (e.g., Lund & Thrane, 1983).…”
Section: Introductionmentioning
confidence: 93%
“…The study showed that students who had the most academically oriented education gained more in general intelligence compared to those with the least amount of academic education. Several similar studies have been carried out on Swedish data (e.g., Balke-Aurell, 1982;Gustafsson, in press;Husén & Tuijnman, 1991). There also are other such studies, several of which are Scandinavian (e.g., Lund & Thrane, 1983).…”
Section: Introductionmentioning
confidence: 93%
“…También, automaticidades que liberan tiempo y conciencia: una persona puede ejecutar más rápido y pensando en varias cosas a la vez. Ellas construyen a su vez excelencia educativa, meritocracia, autonomía, creatividad y soberanía intelectual => límits of lear-ning, endstates (Bloom, 1968(Bloom, , 1972(Bloom, , 1978(Bloom, , 1985Husen, 1988, Husen & Tuijnman, 1991Gardner, 1994;Sternberg & Grigorenko, 2001;Zhang & Sternberg, 2006).…”
Section: Modelos Teóricos Conceptualizaciones Focosunclassified
“…General ability enhances individual's cognitive abilities through declarative knowledge or "what to do" (Cauley 1986). In addition, it helps in 1) the retention of information (Conway et al 1991) 2) application of acquired information outside classroom situations (Cole et al 1976 3) the development of general problem solving capacity (Husen and Juijnman, 1991). One particular aspect of increased level of formal education is its relationship with cognitive ability.…”
Section: Perception Of Entrepreneurial Abilitymentioning
confidence: 99%